Ion kinetic effects linked to magnetic field discontinuities in the slow Alfvénic wind observed by Solar Orbiter in the inner heliosphere - Perrone, Denise; Settino, Adriana; De Marco, Rossana; D’Amicis, Raffaella; Perri, Silvia (Frontiers in Astronomy and Space Sciences, 2023)
Slow solar wind, sharing magnetic and plasma properties typical of fast wind, the so-called slow Alfv énic wind, has been widely observed in the heliosphere. Here, we report an analysis of the turbulent properties of a slow Alfv énic stream observed by Solar Orbiter at 0.64 AU.This solar wind stream is characterized by well distinguishable regions, namely a main portion, an intermediate region, and a rarefaction region. Each of those intervals have been studied separately, in order to enhance similarities and differences in their turbulence properties. Coherent structures naturally emerge over different time/spatial scales and their characteristics at ion scales have been investigated. The presence of these intermittent events have been found to be closely related to kinetic features in the ion (both proton and alpha particles) velocity distribution functions, suggesting a fundamental role in the kinetic physical processes that mediate the sub-ion turbulence cascade.